2006
DOI: 10.1590/s0102-09352006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Indução da ovulação em cabras, fora da estação reprodutiva, com LH e GnRH e com estro induzido por progestágenos

Abstract: Indução da ovulação em cabras, fora da estação reprodutiva, com LH e GnRH e com estro induzido por progestágenos [Induction of the out-of-season ovulation (with LH and GnRH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Leite et al (2006) reported that a 66.6% estrus rate is considered satisfactory for goats. Fonseca et al (2003) reports that the estrus induction response in goats can vary from 60% to 100%, based on the individual and environmental factors, animal health, and nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Leite et al (2006) reported that a 66.6% estrus rate is considered satisfactory for goats. Fonseca et al (2003) reports that the estrus induction response in goats can vary from 60% to 100%, based on the individual and environmental factors, animal health, and nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in all groups are satisfactory and is within parameters recommended in the literature. Leite et al (2006) have reported that a 66.6% estrus rate is considered satisfactory for caprine species. Souza et al 2011, report that estrus detection is of great value for both artificial insemination and natural coverage.…”
Section: Discussionmentioning
confidence: 99%